ASSESSMENT OF NURSES KNOWLEDGE AND PRACTICE TOWARDS THE CARE AND MANAGEMENT OF INTRAVENOUS CANNULA - Usama Siddique1 , Shafiullah2 , Atta ullah3 , Haya ul Batool Abbasi4 , Meena Luther5 , Noman dilshad6 , Amir Sultan7, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: In peripheral intravenous cannulation (PIC), a temporary plastic tube is inserted into a vein through a puncture in the patient's skin using a needle for fluid therapy, parental nutrition, and blood. Objective: The study was conducted with the aim of determining the knowledge and attitude of nurses towards intravenous cannulation. METHODOLOGY: A descriptive cross-sectional study was conducted with a sample size of 176 nurses collected from November 2022 to march 2023 in the Saidu Group of Teaching Hospital Swat (SGTH) through sample random sampling. A valid and reliable questionnaire was used for data collection that contains three parts. A descriptive statistic of categorical and continuous variables was calculated, while an independent t-test was used for the association between knowledge and attitude with demographic variables using SPSS 22.0. RESULTS: The total number of participants in the study was 176, while the number of female participants was in the majority (58%) compared to male nurses (42%). The majority of the participant’s knowledge was good (77%), while 23% of the knowledge was poor. The nurse’s practice of IV cannulation was good (82%), while the remaining 18%'s practice was poor. The mean score of knowledge of male nurses was better (1.2 ± 0.18) than that of female nurses (1.1 ± 0.15), while the mean score of practices of female nurses was higher (3.9 ± 0.31) than that of male nurses (3.8 ± 0.34). In the category of education, the mean score of MSN nurses was higher in both knowledge (1.4 ± 0.1) and practice (4.1 ± 0.1). CONCLUSION: The study concluded that nurses have good knowledge of intravenous cannulation and that their practice is good. The study further concluded that males have good knowledge of intravenous cannulation, while females' level of practice towards IV skills is high. Furthermore, it is concluded that gender affects knowledge because it is highly significant. While age, education, and experience affect the practice of nurses and are highly significant.